2021
DOI: 10.1073/pnas.2013452118
|View full text |Cite
|
Sign up to set email alerts
|

E2A-regulated epigenetic landscape promotes memory CD8 T cell differentiation

Abstract: During an acute viral infection, CD8 T cells encounter a myriad of antigenic and inflammatory signals of variable strength, which sets off individual T cells on their own differentiation trajectories. However, the developmental path for each of these cells will ultimately lead to one of only two potential outcomes after clearance of the infection—death or survival and development into memory CD8 T cells. How this cell fate decision is made remains incompletely understood. In this study, we explore the transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 69 publications
2
11
0
Order By: Relevance
“…The major outlier was the central memory cluster, which was almost entirely (>97%) composed of singlet clones. Although it may be possible that some of the cells in this cluster were actually naïve cells, given that naïve and memory T cells share many transcriptomic and epigenetic similarities ( Schauder et al, 2021 ), the splenic CD8 T cells we sequenced were sorted to be CD44 + ( Fig S1B ); these data therefore suggest that central memory CD8 T cells may undergo clonal contraction. In general, splenic CD8 T cell clusters were less clonally expanded than those in the islets, as would be expected given that the islets are the major source of autoantigens in T1D.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major outlier was the central memory cluster, which was almost entirely (>97%) composed of singlet clones. Although it may be possible that some of the cells in this cluster were actually naïve cells, given that naïve and memory T cells share many transcriptomic and epigenetic similarities ( Schauder et al, 2021 ), the splenic CD8 T cells we sequenced were sorted to be CD44 + ( Fig S1B ); these data therefore suggest that central memory CD8 T cells may undergo clonal contraction. In general, splenic CD8 T cell clusters were less clonally expanded than those in the islets, as would be expected given that the islets are the major source of autoantigens in T1D.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we identified central memory and anergic cells in the spleen, both of which had limited clonal expansion and predicted differentiation potential. Although the splenocytes we sequenced were sorted on CD44 + cells, it may be possible that the splenic central memory cluster may also contain some naïve CD8 T cells given that naïve and memory CD8 T cells share similar phenotypic and epigenetic profiles ( Schauder et al, 2021 ). Collectively, our data therefore identify previously underappreciated phenotypic heterogeneity among diabetogenic CD8 T cells and show that several different CD8 T-cell populations exist in the islets and spleens of NOD mice during the onset of T1D.…”
Section: Discussionmentioning
confidence: 99%
“…From this report, it is clear that Suv39h1-mediated H3K9me3 deposition creates an epigenetic barrier on the stem/memory gene expression program in the effector cells and thus regulates the fate of T cell differentiation [ 102 ]. To better understand the CD8 + T cell fate decision following activation, another study was performed on antigen-specific CD8 + T cells during an acute infection with LCMV [ 103 ]. scRNA-seq revealed that short-lived effector cells (SLECs) lose accessibility at Tcf7 (Tcf1)- and Tcf3-occupied enhancers, which regulate genes critical for memory T cell differentiation, and these cells are therefore unable to form long-lived memory T cells [ 103 ].…”
Section: Epigenetic Changes During T Cell Differentiationmentioning
confidence: 99%
“…To better understand the CD8 + T cell fate decision following activation, another study was performed on antigen-specific CD8 + T cells during an acute infection with LCMV [ 103 ]. scRNA-seq revealed that short-lived effector cells (SLECs) lose accessibility at Tcf7 (Tcf1)- and Tcf3-occupied enhancers, which regulate genes critical for memory T cell differentiation, and these cells are therefore unable to form long-lived memory T cells [ 103 ]. On the other hand, memory precursor effector cells (MPECs) sustain chromatin accessibility at enhancers, which are highly enriched for Tcf3 (E2a) binding sites and are important for memory-related gene expression [ 103 ].…”
Section: Epigenetic Changes During T Cell Differentiationmentioning
confidence: 99%
See 1 more Smart Citation